PREDIKTIVNE VRIJEDNOSTI MORFOLOŠKIH KARAKTERISTIKA NA REZULTATE SITUACIONIH TESTOVA U NOGOMETU - Alen Kapidžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Main goal of this research is to identify influence of morpholgy characteristics abilities on results of situational in soccer play. Research has been applied on 155 students - 1st and 2nd year of Faculty of sport and physical education in Tuzla, age 19-22. To identify the influence of applied tests we used regression analisys. . In this research we use 21 variables of morpholgy characteristics which present prediction system and group of 9 situation motoric tests in soccer play which presents system of criteria variables.